Ileovesical fistula secondary to chemotherapy for follicular non-Hodgkin lymphoma: A case report and review of the literature - Zülfikar KARABULUT; Hampar AKKAYA; Mustafa Burak HOŞÇAN; Gökhan MORAY (Turkish Journal of Gastroenterology, 2019)
-